PERMAINAN WHATâS IN HERE? SEBAGAI ALTERNATIF METODE PEMBELAJARAN UNTUK MELATIHKAN KETERAMPILAN BERTANYA SISWA SEKOLAH DASAR - Suraya, Selly Nurina (Premiere Educandum, 2014)
Education is a systematic process to improve human dignity in a holistic manner that allows self potentials (affective, cognitive, and psychomotor) develop optimally. Curriculum 2013 adheres to the basic view that knowledge cannot be moved away from the teacher to the learner. For learners, learning should be shifted from "notified" to "actively seek out". One of methods that can be applied is a game âWhats in here?â, that is learning with the game questions that make students happy to learn but it is also able to educate students to be more creative thinking and develop knowledge. The game âWhats In Here?â can be used as an alternative method of teach for training elementary school students to have questioning skills.Keywords: questioning skills, game âWhats in Here?â elementary school students